Negative emission power plants: Techno-economic analysis of a biomass-based integrated gasification solid oxide fuel cell/gas turbine system for power, heat, and biochar co-production—part 2 - Jaiganesh, N.; Kuo, Po-Chih; Champatan, Vipin; Gopi, Girigan; Kumar, R. Ajith; Aravind, P.V. (Frontiers in Energy Research, 2022)
Bioenergy with carbon capture and storage (BECCS) represents one of the few concrete and economic means for the removal of CO2 present in the atmosphere in large scale along with the simultaneous production of electrical power output. Techno-economic analyses are carried out to study the effect of biochar co-production in biomass-based integrated gasification solid oxide fuel cell system with carbon capture and storage (BIGFC/CCS) unit using air and steam-oxygen as gasification medium. Levelized cost of electricity (LCOE), net present value (NPV), payback period, internal rate of return (IRR) and levelized cost of negative carbon (LCNC) are the key economic parameters chosen for the present study. We analyzed the techno-economic performance of the system under various operating conditions of the power plant that includes the change of gasification agents as well as the proportion of biochar co-production on mass basis (either for the given electrical power output or for the given biomass feed). We found that the total overnight cost (TOC) for the air and steam-oxygen gasification BIGFC/CCS systems are estimated as 6197 /kW and 5567 /kW, respectively. Steam-oxygen gasification system is found to be economically beneficial compared to air gasification method for all the cases studied. The sensitivity analysis is further carried out for the identified economically viable biochar co-production case to study the influence of capital cost, operating cost, biomass cost, plant capacity factor and tax. The influence of carbon credit scenario on the economic indicators is also reported. The most effective economic performance from the steam-oxygen gasification of BIGFC/CCS system for 10% biochar co-production on mass basis for the given electrical power output reported an NPV of 3542 M,IRR of 24.2% ,payback period of 3.3 years with LCNC of -322.5/t of CO2.